2011
DOI: 10.5114/aoms.2011.25566
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren prevents and ameliorates metabolic syndrome in fructose-fed rats

Abstract: IntroductionThe renin-angiotensin system plays a major role in the pathogenesis of metabolic syndrome. The objective of this study was to examine the effects of aliskiren, a direct renin inhibitor, on the metabolic syndrome of fructose-fed rats.Material and methodsMale Sprague-Dawley rats were divided into 4 groups (n = 6 for each group). Group Con: rats were fed a standard chow diet for 8 weeks, group Fru: rats were fed a high fructose diet (60% fructose) for 8 weeks, group FruA: rats were fed a high fructose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Although some of the studies reported role of visceral obesity in fructose-induced insulin resistance, in our study, as we have not observed visceral obesity, contribution of it to the observed insulin resistance in our study might be negligible. Korandji et al [27] reported feeding of 60–65% fructose diet increases fasting plasma glucose after one week, whereas Padiya et al [28] and Chou et al [31] reported the similar observation after 4 to 8 weeks of fructose-feeding. Masterjohn et al [26] and Leibowitz et al [32] reported no effect of fructose-feeding on glucose levels after 5 to 9 weeks of feeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some of the studies reported role of visceral obesity in fructose-induced insulin resistance, in our study, as we have not observed visceral obesity, contribution of it to the observed insulin resistance in our study might be negligible. Korandji et al [27] reported feeding of 60–65% fructose diet increases fasting plasma glucose after one week, whereas Padiya et al [28] and Chou et al [31] reported the similar observation after 4 to 8 weeks of fructose-feeding. Masterjohn et al [26] and Leibowitz et al [32] reported no effect of fructose-feeding on glucose levels after 5 to 9 weeks of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of human studies reported that fructose intake is positively correlated with total cholesterol levels when the daily intake of fructose is more than 100 g per day but not when the intake is less than that, suggesting the critical role of fructose quantity in regulating plasma cholesterol levels [34]. Majority of the studies on SD rats reported no change in plasma total cholesterol levels after fructose-feeding [26, 28], whereas Chou et al showed increased levels after four weeks of fructose-feeding [31]. In contrast to this report, we have not observed any increased total cholesterol after 4 weeks of fructose-feeding, but we observed a small increase in plasma total cholesterol levels at 12 weeks of fructose-feeding but they reached normal levels after 24 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides the rationale for the use of renin inhibitors for the treatment of hypertension, cardiovascular and kidney diseases. Animal studies revealed that aliskiren has favorable metabolic profile in patient with metabolic syndrome by improving glucose tolerance and insulin sensitivity [29, 30]. …”
Section: Introductionmentioning
confidence: 99%